2010
DOI: 10.1017/s0305000910000425
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between lexical and phonological development in young children*

Abstract: Our understanding of the relationships between lexical and phonological development has been enhanced in recent years by increased interest in this area from language scientists, psychologists and phonologists. This review article provides a summary of research, highlighting similarities and differences across studies. It is suggested that the research falls into two categories with different goals and different methodological approaches: (1) child-centered studies that examine the influences active in the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

24
283
3
18

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 305 publications
(342 citation statements)
references
References 74 publications
24
283
3
18
Order By: Relevance
“…During phonological development, the baby develops vocal play and later on certain babbling sequences that serve as the building blocks for latter word production [2]. Babies with cleft palate have a disadvantage during this vocal development since the palate is not yet repaired at these stages and they have to engage in the vocal practice with a cleft palate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During phonological development, the baby develops vocal play and later on certain babbling sequences that serve as the building blocks for latter word production [2]. Babies with cleft palate have a disadvantage during this vocal development since the palate is not yet repaired at these stages and they have to engage in the vocal practice with a cleft palate.…”
Section: Introductionmentioning
confidence: 99%
“…He also mentioned some research findings indicating that children, who have difficulty learning phonology, show similar difficulties for learning morphological, syntactic, and semantic regularities of language as well. It has also been recognized that there is a bidirectional relationship between phonology and language processing in children who are developing language [2].…”
Section: Introductionmentioning
confidence: 99%
“…The authors found that phonological complexity plays an important role in that words with late-acquisition phonemes and syllable structures are produced with greater variability and both the frequency of lexical types and the phonological similarity influence the observed variability in speech-the greater the effect of frequency of lexical type and phonological similarity, the less variability in productions. In addition, children with large vocabularies have phonological systems more complex than those with small vocabularies, since the larger amount of words produced can generate the requirement of a more advanced phonological system (6) . A recent study (7) revealed that children in the early stages of phonological acquisition select the words they will say based on how "pronounceable" they are.…”
Section: Introductionmentioning
confidence: 99%
“…Sanojen ymmärtämisen voidaan normaalitilanteessa odottaa alkavan 7-10 kuukauden iässä (Fenson ym., 1994;Harris, Yeeles, Chasin & Oakley, 1995;Kuhl, 2007) tai jopa tätä aiemmin (Bergelson & Swingley, 2012). Sanojen tuottaminen alkaa keskimää-rin 12 kuukauden iässä (Clark, 2009, s. 14;Fenson ym., 1994;Stoel-Gammon, 2011), mutta yksilöllinen vaihtelu on suurta. Suomalaistutkimuksessa (Stolt, Haataja, Lapinleimu & Lehtonen, 2008) lapset tuottivat 12 kuukauden iässä keskimäärin neljä sanaa, kun ymmärrettyjen sanojen keskiarvo oli jo 94.…”
unclassified
“…Yksilöllisillä eroilla lasten kehityksessä ja vuorovaikutuksen aikaisessa toiminnassa saattaa olla merkitystä siinä, minkälaiseksi lapselle suunnattu puhe muotoutuu. Aiheen tutkimus on tärkeää siksi, että yksilölliset erot varhaisessa sanaston kehityksessä ovat merkittävät (Clark, 2009, s. 14;Fenson ym., 1994;Stoel-Gammon, 2011;Stolt ym., 2008). Lisäksi on huomionarvoista, että tietty lapselle suunnatun puheen piirre saattaa olla jossain vaiheessa merkityksellinen lapsen puheen kehitykselle, mutta myöhem-min vastaavaa funktiota ei välttämättä ole (mm.…”
unclassified